Analisis Konsumsi Layanan SPA Di Era Baru, Perspektif Theory of Planned Behavior (TPB) - Putu Saroyini Piartrini (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2020)
Present study predict intention to engage in SPA in Post Pandemi situation from Planned Behavior Theory, extended with Perceived Risk as predictors. Data were accumulated from 390 SPA customers who engaged in SPA treatment in Kuta and Ubud as main destination of foreign visitors. data analysis uncovered that attitude, subjective norms , perceived behavioral control and perceived risk significantly affected intention to engage in SPA treatment. to encourage intention to engage in SPA treatment provider needs to implement health and security procedures consistently because higher perceived risk will lessen intention to engage in SPA treatment.